Pengaruh Ukuran Partikel Terhadap Solubilisasi Metronidazol dengan Menggunakan Brij 35 - Febriyenti, Febriyenti; Halim, Auzal; Nelvianti, Nelvianti (Jurnal Farmasi Andalas, 2013)
A Study has been done on the effect correlation effect of particle size on solubilization of metronidazol using brij 35 in water solvent. Surface tension method using Torsion Balance Type OS White. Inst. Co. Ltd and refraction method using Refractometer ABBE were done for determination of CMC (Critical Micelle Concentration) values of surfactans with Brij 35. Size of metronidazol particle was reduced by milling process with various duration 0 hour, 1 hour, 6 hours and 12 hours using Ball Mills âThe Pascall Engineeringâ. Result showed that concentration of metronidazol in solubilization was 11,0888 mg/ml, 10,6470 mg/ml, 10,4431 mg/ml and 10,0890 mg/ml respectively at various milling period of 1 hour, 6 hour, 12 hour and without milling. Metronidazol after milling for 1 hour showed better solubilization than without milling with further. The Solubilization of metronidazol decreased with an increase in milling time. The Results at various time of milling process of 1 hour, 6 hours, 12 hours and without miliing. Process found the solubilization of metronidazol concentration were 11,0888 mg/ml, 10,6470 mg/ml, 10,4431 mg/ml and 10,0890 mg/ml. Keywords : Solubilization, Metronidazol, Brij 35, milling